2021
DOI: 10.1016/j.tifs.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on food habits and perceptions: A study with Brazilians

Abstract: Background Following the COVID-19 pandemic (caused by the SARS-CoV-2 coronavirus) at the beginning of 2020, containment measures have been taken by different countries around the globe. Citizens were forced to stay in quarantine, affecting their food consumption habits and food sector. These impacts have not yet been properly understood. Thus, it is important to describe the consequences of COVID-19 on food consumption habits globally, especially in the context of developing countries, such as Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Interviewees perceived that such activities were enabled by the increase of citizens' free time which highlights the interaction of the food system with other systems ( Geels, 2011 ) and the relevance of time for citizens to be able to participate in the food system actively (e.g., Tregear, 2011 ). This is in line with other studies that found that due to the closure of the gastronomy sector in many countries and the sudden time availability, people started to cook more and, in some cases, be more conscious about the food they purchased (see, for example, Hobbs (2020) , Ferreira Rodrigues et al (2021) , and Molina-Montes et al (2021) ). Actors from the regime sub-system also contributed to the community good, e.g., by donating food after the gastronomy sector's closure so it would not go to waste (resource sub-system) or directly donating gastronomy vouchers (citizens).…”
Section: Discussionsupporting
confidence: 92%
“…Interviewees perceived that such activities were enabled by the increase of citizens' free time which highlights the interaction of the food system with other systems ( Geels, 2011 ) and the relevance of time for citizens to be able to participate in the food system actively (e.g., Tregear, 2011 ). This is in line with other studies that found that due to the closure of the gastronomy sector in many countries and the sudden time availability, people started to cook more and, in some cases, be more conscious about the food they purchased (see, for example, Hobbs (2020) , Ferreira Rodrigues et al (2021) , and Molina-Montes et al (2021) ). Actors from the regime sub-system also contributed to the community good, e.g., by donating food after the gastronomy sector's closure so it would not go to waste (resource sub-system) or directly donating gastronomy vouchers (citizens).…”
Section: Discussionsupporting
confidence: 92%
“…Among our sample, food purchase patterns were also affected by the pandemic. We found that online food purchases increased; this was also reported in France, Brazil, and Morocco ( 17 , 36 , 43 ). Online food purchases can have a beneficial impact, since the shopper is not exposed to all of the store's marketing strategies, food cravings are reduced by not seeing the real food, and there is no immediate gratification ( 44 ).…”
Section: Discussionsupporting
confidence: 80%
“…Studies from Latin America and Europe consistently reported that there was an increase (measured or self-perceived) in the intake of legumes (15,20,31). Many studies reported an increase in fruits and vegetables (20,(31)(32)(33)(34)(35)(36), with few studies finding a decrease (17,37). Results were mixed for snacks/sweets, with some studies reporting a decrease (15,37), and others an increase (16,31,33,38).…”
Section: Discussionmentioning
confidence: 99%
“…Concern regarding food safety (results = 32) and risk perception (results = 31) were the motivators with the highest number of results among all categories and motivators. Regarding concerns regarding food safety, we can observe, for example, (a) greater concern with food safety and hygiene practices during the COVID-19 pandemic [75] (Brazil); (b) concern regarding pesticides [64] (India); and (c) food safety concerns that are inconsistent with selfreported practices [40] (South Africa). As expected, mixed results were observed for risk perception.…”
Section: Hazards and Motivators Of Food Safety Perceptionmentioning
confidence: 99%